Hexagon Fraud Detection of Regional Government Financial Statement as A Fraud Prevention on The Pandemic Crisis Era - Shinta Permata Sari; Nikmar’ati Khoiriah (Wacana Journal of Social and Humanity Studies, 2021)
The COVID-19 pandemic has paralyzed the world economic sectors in many countries, including Indonesia. Data from the Fiscal Policy Office of the Indonesia Ministry of Finance shows that economic contraction due to the pandemic has reached -5,32% in Q2 2020. In line with that increasing losses, the potential of fraudulent financial reporting by local governments can be increased if there are no strict supervision and detection.  The newest  Fraud  Hexagon  Model of  Vousinas (2019) is used to detect all factors of fraud in local government financial statements.  Fraud Hexagon presents pressure, opportunity, rationalization, competence, arrogance, and collusion as the factors of fraud detection. This study analyzes the local government financial statements of district/city government in East Java Provence, Indonesia from 2014-2018 as a sample that is obtained through the purposive sampling methods. Data analysis using logistic regression analysis and the results show that pressure (financial stability and financial targets), opportunity (ineffective monitoring ), competence, and arrogance affect the fraudulent of local government financial statements. Meanwhile, the results also present that pressure  (external pressure),  rationalization, and collusion do not affect the fraudulent of local government financial statements.